Transformasi Perpustakaan Berbasis Inklusi Sosial UPT Perpustakaan Proklamator Bung Karno Dalam Meningkatkan Kesejahteraan Masyarakat - Handayani, Sri; Mutiara, Nisa (Otonomi, 2025)
A library’s transformation based on social inclusion can be understood as a library that offers information services open to a whole community with a variety of backgrounds, characteristics, abilities, status, condition, ethnicity and culture to develop its own potential to support economic well-being. This qualitative research was carried out at UPT Perpustakaan Proklamator Bung Karno Library to find out the implementation of transformation of library based on social inclusion, obstacles encountered and efforts to optimize in order to improve the well-being of the public. The results of the research indicate that library transformation base on social inclusiveness has been well implemented with some obstacles the number of participants exceeds the available capacity, budget constraints, the distribution of participants is not even, including not reaching disability, the limitation of competent sources, the absence of training or refreshment to the committee (SDM), limited activities in training, not continuing on the accompaniment of management, marketing, until market availability according to product segments or business matching, and the stigma of the community that the library is an exclusive place raises reluctance to visit. The optimization of the library transformation program based on social inclusion has been carried out in a manner; conducted pre and post test as well as public satisfaction survey on the implementation of library Transformation activities based on Social inclusion, measurement of success rates and search of impact story data of the training results followed, conducted evaluation process of each end of the activity to see the existing shortcomings and then improved on the subsequent activities, performed a study on the impact of the resulting of the activities of the transformation of libraries based on social inclusion on the community who become participants of such activities, as well new improvements every year.